Determinants of public–private partnership policies. Issue 8 (2nd August 2020) - Rosell, Jordi; Saz-Carranza, Angel
ABSTRACT: This article analyses the determinants of a country's PPP policies. Using the World Bank's 135-country Procuring Infrastructure PPPs 2018 database, we examine the role of legal traditions, European Union membership, transparency and macroeconomic indicators on the policies governing the adoption, procurement and management of PPPs in infrastructures. We find that transparency has a positive effect on the quality of PPP policies. Scandinavian countries are reluctant to enter into PPPs, while European Union legislation has a positive impact only on the procurement process. Macroeconomic indicator effects are weak on PPP score; larger government's revenues reduce country's PPP appetite.